Atrial Fibrillation - Vinall, Phil (MD Conference Express, 2015)
The Einthoven Lecture, presented by Prof Günter Breithardt, focused on atrial fibrillation (AF) and reviewed the history, mechanisms, and pathogenesis of AF. He focused on the association of metabolic syndrome and obesity with AF. These associations provide evidence that supports treatment strategies designed to prevent the development of AF.